Campuran Herbisida Glifosat dan Pupuk Urea Pada Beberapa Taraf Dosis Pada Untuk Mengendalikan Gulma Alang-alang (Imperata cylindrica L.) - Eva Rianti; Bhaidawi Bhaidawi; Abdullah Abdullah (Faculty of Agriculture, Universitas Malikussaleh, 2017)
Imperata weeds are very difficult to control. It is because the weeds have ability to regenerate rapidly through the stolon and seed. Weed control in principle is an effort to increase the competitiveness of basic crops and weaken the competitiveness of weeds. The use of glyphosate herbicide can be mixed with other ingredients; one of them is urea fertilizer. This study aims to reveal whether the mixture of glyphosate herbicide and urea fertilizer at several doses can suppress weed growth. This study used Randomized Block Design factorial pattern, with two factors: (1) dose factor of glyphosate (G); G0 (control), G1 (glyphosate 100 ml liter), and G2 (200 ml liters of glyphosate). (2) urea fertilizer (P); P0 (control), P1 (urea 400 gram), and P2 (urea 600 gram). The results showed that the mixture of glyphosate herbicide and urea fertilizer can suppress the growth and development of imperata weeds. The best treatment was found in a mixture of 200 ml of glyphosate herbicide and urea fertilizer at a dose of 600 grams, while the lowest treatment was found in the control